2021
DOI: 10.3390/pr9111929
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Introduction to the Polyurethanes According to the Principles of Green Chemistry

Abstract: Polyurethanes are most often called “green” when they contain natural, renewable additives in their network or chemical structure, such as mono- and polysaccharides, oils (mainly vegetable oils), polyphenols (e.g., lignins, tannins), or various compounds derived from agro-waste white biotechnology (Principle 7). This usually results in these polyurethanes obtained from less hazardous substrates (Principle 4). Appropriate modification of polyurethanes makes them susceptible to degradation, and the use of approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 112 publications
0
14
0
Order By: Relevance
“…To replace polyols made from petroleum, BioBased Technologies (previously Cargill) created a commercial technology for turning vegetable oils into polyols. The moderate process conditions also reduce the reliance on non-renewable feedstocks and save energy [125]. These are some examples showing how bioplastics are increasingly becoming part of our everyday life, but many improvements are still needed.…”
Section: Use Of Renewable Feedstocksmentioning
confidence: 99%
“…To replace polyols made from petroleum, BioBased Technologies (previously Cargill) created a commercial technology for turning vegetable oils into polyols. The moderate process conditions also reduce the reliance on non-renewable feedstocks and save energy [125]. These are some examples showing how bioplastics are increasingly becoming part of our everyday life, but many improvements are still needed.…”
Section: Use Of Renewable Feedstocksmentioning
confidence: 99%
“…26–28 In this sense the development of monomers with potential bio-based origin and good performance is attracting a lot of attention as an alternative towards a carbon-neutral and circular polymer industry. 29–37…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] In this sense the development of monomers with potential bio-based origin and good performance is attracting a lot of attention as an alternative towards a carbon-neutral and circular polymer industry. [29][30][31][32][33][34][35][36][37] Among all the renewable resources available, lignin represents one of the most abundant biopolymers as it is present in all vascular plants along with cellulose and hemicellulose. [38][39][40] These three biopolymers are present in different distributions depending on the plant.…”
mentioning
confidence: 99%
“…Polysaccharides, as polymers of monosaccharides, are one of the most abundant carbohydrates in living organisms, like plants, animals, microorganisms, and marine organisms. [1] Polysaccharides serve multiple bioactivities, including anti-oxidation, anti-cancer, immunomodulation, and antidiabetic. [2,3] Several studies showed that the properties of polysaccharides, like abundant, relatively nontoxic, renewable, and bioactive make them promising applications in food, medicine, and material industries.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides, as polymers of monosaccharides, are one of the most abundant carbohydrates in living organisms, like plants, animals, microorganisms, and marine organisms [1] . Polysaccharides serve multiple bioactivities, including anti‐oxidation, anti‐cancer, immunomodulation, and antidiabetic [2,3] .…”
Section: Introductionmentioning
confidence: 99%